Metode Pembelajaran Gamelan Selonding Pada Sekaa Gong Sabha Winangun, Dalam Siatuasi Pandemi Covid-19 - I Wayan Sukadana; I Komang Alit Juniarta; I Nyoman Winyana (UNHI PRESS, 2021)
Education innature means generally includes all the efforts and deeds of the old generation to transfer their experience, knowledge, their wealth and skills to the younger generation to enable them to perform their life functions inthe same association as best aspossible. The covid-19 pandemic in May 2020, causing the paralysis of all sectors of life including the Education sector. Nonformal education becomes one of the alternative options for students to fill their free time, one of which is learning gamelan. Learning Gamelan Selonding is one of non-formal education. Based on this, the problems that can be proposed are: How the Method of Learning Gamelan Selonding On Sekaa Gong Sabha Winangun In Siatuasi Pandemic Covid-19To dissect the problem is used Constructivism Theory. Data is collected by observation, interview, and study of document results. After the data is collected then analyzed with qualitative descriptive techniques. The results of this study in the form of Gamelan Selonding Learning Method is the first strategy to introduce gamelan selonding including the names of instruments, always reminding to obey prokes such as using masks during training, washing hands before arranging gamelan and approaching by teaching positive habits. The second is preparing methods to convey gending materials, especially during the current pandemic such as audio visual methods, listening methods, sectoral methods.